“Death Parade” on Victory Day (Minsk, 2020) - Lastouski, Aliaksei (Institute of National Remembrance Review, 2021)
Being borrowed from the Soviet historical narrative and successfully adapted to the needs of the Belarusian state, the memory of Victory in the Great Patriotic War has become the ideological basis for the authoritarian regime in Belarus. This article is aimed at addressing the celebration of the Victory Day in Minsk in 2020 and, through the analysis of this particular case, identify the main frames for the ideological image of Victory in the Belarusian authorities’ politics of history as well as the mechanisms for population involvement and ideological mobilisation. The year 2020 has become critical for Belarusian politics as for the first time since 1994, mass democratic protests challenged Aliaksandr Lukashenka’s complete control over Belarusian society.